Effects of Combined Training on Isokinetic Strength of Ankle, Knee, Lumbar and Shoulder in Female Professional Volleyball Players - Jong-Hak Lee; Ho-Seong Lee; Jae-Chung Ghil (Asian Society of Kinesiology, 2019)
OBJECTIVES The purpose of this study was to investigate the effects of combined training on isokinetic strength of ankle, knee, lumbar and shoulder in female professional volleyball players. METHODS Twenty-five female professional volleyball players were divided to combined training group (CTG, n=14) and control group (CON, n=11). Combined training was performed for 70 min/day (warm-up; 15 min, plyometric training; 20 min, core balance training; 20 min, cool-down; 15 min), 2 times a week for 8 weeks. Isokinetic strength for each region measured before and 8 weeks after combined training. RESULTS In peak torque, right ankle evertor and invertor, left ankle evertor and invertor, right knee extensor and flexor, left knee extensor and flexor, lumbar extensor and flexor, right shoulder internal rotator, left shoulder internal rotator were statistical significant interactions between G, T and G×T, respectively. In peak torque/body weight, right ankle evertor and invertor, left ankle evertor and invertor, right knee extensor and flexor, left knee extensor and flexor, lumbar extensor and flexor, right shoulder external rotator and internal rotator and left shoulder internal rotator were statistical significant interactions between G, T and G×T, respectively. In total work, right ankle evertor and invertor, left ankle invertor, right knee extensor and flexor, left knee flexor, lumbar extensor and flexor, right shoulder external rotator and internal rotator, left shoulder external rotator and internal rotator were statistical significant interactions between G, T and G×T, respectively. CONCLUSIONS We demonstrated that combined training increases the isokinetic strength of ankle, knee, lumbar and shoulder in professional female volleyball athletes.